Impact of imitation abilities on social communication in autistic children: evidence from an Early Start Denver Model intervention study - Shihua Xiao; Jing Li (Molecular Autism)
Abstract Imitation is foundational to early social learning, yet autistic children often exhibit significant impairments in imitation, potentially impacting their social communication skills. This study examined the relationship between imitation abilities and social communication in autistic children and evaluated the effectiveness of the Early Start Denver Model (ESDM) intervention. The study included 52 autistic children aged 2–5, divided into an experimental group receiving ESDM intervention and a control group undergoing standard rehabilitation. We assessed the children’s imitation and social communication skills before and after the intervention. Results indicated a significant positive correlation between imitation and social communication skills both before and after the intervention. Specifically, various forms of imitation (e.g., vocal, gestural, object-related) were closely linked to different domains of social communication (e.g., expressive communication, joint attention, social skills). Baseline imitation levels and improvements in imitation were significant predictors of enhanced social communication, jointly accounting for over half of the observed improvements in social communication, with imitation improvement being the strongest predictor. Age positively moderated the relationship between imitation and social communication, with older children showing a stronger impact of imitation on social communication. Although these effects were evident across groups, the ESDM group showed greater gains in imitation skills compared to the control group. However, we did not find evidence of an intervention effect on social communication skills. This study underscores the critical role of imitation in the social communication development of autistic children. These findings support the enhancement of imitation skills in early interventions for autistic children, highlighting the effectiveness of ESDM in fostering imitation abilities.